Effect of skin fibroblast-derived allogeneic feeder cells on porcine ES-Like cell establishment - Sasithorn Panasophonkul (2018)
In the present study, the effect of two types of allogeneic-derived feeder cells [porcine ear and tail skin fibroblasts (PESF, PTSF)] and three types of xenogeneic-derived feeder cells [human foreskin fibroblasts (HFK), mouse embryonic fibroblasts (MEF) and immortalized mouse embryonic fibroblasts (STO)] on the isolation and cultivation of putative porcine embryonic stem cells (pESCs) was evaluated. In vivo derived zona pellucida (ZP)-free blastocysts were cultured on different mitotically inactivated feeder layers. The rates of ICM outgrowth and primary colony formation were observed, and further passage onto new feeders was performed. The characteristics of pESCs, including alkaline phosphatase (AP) activity, and pluripotent-related markers (OCT3/4, NANOG, SSEA-4) and genes were examined. Attached blastocysts cultured on HFK and STO feeders showed a higher percentage of ICM outgrowths than those cultured on PESF (76.7, 72.9 and 38.9%, respectively; P<0.05). The rates of primary ES-like colony formation and the number of putative ESC lines were significantly decreased when ICM outgrowths were cultured on PESF, compared with those cultured on HFK (30.6 vs. 76.7%, respectively; P<0.05). Only ES-like colonies from one (25%) and three (50%) cell lines developed on PTSF and STO feeders, respectively, were further maintained in an undifferentiated morphology associated with the presence of all ES characteristics; however, these characteristics disappeared when colonies were continued to the 8th and 6th passages, respectively. The present study indicated that feeder cell types affect the success of pESC establishment and maintenance of their pluripotency. © 2012 The Japanese Society of Veterinary Science.